EDUKASI TERPADU: PENINGKATAN PENGETAHUAN PENANGANAN HYGINE, STUNTING DAN PENYALAHGUNAAN OBAT-OBAT TERLARANG PADA MASYARAKAT BANJARMASIN UTARA - Amalia, Senya Puteri; Ariani, Novia; Lestari, Desy Ayu; Fawwazi, Muhammad Hafizh Abiyyu Fathin; Ariska, Rizki; Fatimatuzzahrah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Public health issues such as hygiene, stunting, and substance abuse remain significant challenges in Indonesia, including in North Banjarmasin. These conditions affect the quality of life and well-being of the community, requiring an improvement in knowledge regarding the importance of good hygiene practices, stunting prevention in children, and the dangers of substance abuse. Integrated education that covers these various aspects is crucial for raising awareness and understanding among the public in maintaining health, preventing diseases, and fostering a healthier and more productive generation. This study was conducted through outreach programs focusing on the importance of hygiene for elementary school children, the distribution of nutritious food to address stunting in children, and counseling on the dangers of substance abuse for students in North Banjarmasin schools. The results of the study showed a positive response from the target participants, with increased understanding of personal hygiene, the importance of nutrition for stunting prevention, and the harmful effects of substance abuse. Thus, integrated education, such as the approach in this study, has proven effective in improving public knowledge and can serve as a model in efforts to prevent public health issues.